2001
DOI: 10.1007/s004210100387
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stress modulates arterial pressure variability and arterial baroreflex response of heart rate during head-up tilt in humans

Abstract: To examine the effects of thermal stress on the blood pressure variability and the arterial baroreceptor-cardiac reflex during orthostatic stress, 11 male volunteers underwent whole body thermal stress using a cool or hot water-perfused suit during 5 min of 70 degrees head-up tilt (HUT). The spontaneous variability in arterial pressure was quantified by power spectrum analysis. The sensitivity of the arterial baroreceptor-cardiac reflex was calculated from the spontaneous changes in beat-to-beat arterial press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
30
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 33 publications
(44 reference statements)
7
30
1
2
Order By: Relevance
“…Bahjaoui- Bouhaddi et al (2000) have reported that spontaneous cardiac baroreex sensitivity was not changed by 10°HDT during normothermia. However, LBNP or head-up tilt reduces spontaneous cardiac barore¯ex sensitivity (Hughson et al 1994;Yamazaki and Sone 2001). It has been shown that the alterations in the cardiopulmonary baroreceptor loading due to LBNP or LBPP result in changes in the gain of the carotid baroreceptor-cardiac re¯ex (Pawelczyk and Raven 1989;Shi et al 1993).…”
Section: Discussionmentioning
confidence: 98%
“…Bahjaoui- Bouhaddi et al (2000) have reported that spontaneous cardiac baroreex sensitivity was not changed by 10°HDT during normothermia. However, LBNP or head-up tilt reduces spontaneous cardiac barore¯ex sensitivity (Hughson et al 1994;Yamazaki and Sone 2001). It has been shown that the alterations in the cardiopulmonary baroreceptor loading due to LBNP or LBPP result in changes in the gain of the carotid baroreceptor-cardiac re¯ex (Pawelczyk and Raven 1989;Shi et al 1993).…”
Section: Discussionmentioning
confidence: 98%
“…However, the amount of information on the effect of thermal stress on the magnitude and pattern of change in leg volume during postural change remains small. Since orthostatic hypotension during heat stress has been observed frequently even during a short-term orthostatic stress for 5 min or less (Horvath and Botelho 1949;Lind et al 1968;Yamazaki and Sone 2001), there is a need to observe the change of leg volume within a few minutes during postural change.…”
Section: Introductionmentioning
confidence: 99%
“…Acute skin surface cooling immediately before upright tilting in heat-stressed individuals improved orthostatic tolerance relative to heat stress without cooling 102) . This effect is likely related to profound cutaneous vasoconstriction and the associated redistribution of blood flow from the cutaneous circulation to the central circulation, resulting in increased CVP 103,104) , pulmonary capillary wedge pressure 104) , and baroreflex sensitivity 52,61) during cold stimulus.…”
Section: Cooling Of the Bodymentioning
confidence: 99%